THE ONLINE ENGLISH TEACHING DURING THE PANDEMIC TIME AT JUNIOR HIGH SCHOOLS IN PEKALONGAN - Agustina, Dwi; Matra, Sarlita Dewi; Karimah, Sayyidatul (J-ELLiT (Journal of English Language, Literature, and Teaching), 2021)
Abstract: In 2020 many schools in Indonesia were required to do online teaching practices to prevent the spread of covid-19. Schools in Pekalongan City were the examples. Teachers and students suddenly had to adapt to online classes. As online classes were quite new for the teachers in Pekalongan, the writers were interested in revealing teachers’ actual perceptions and implementation of online classes through a quantitative study. Employing an online questionnaire, this study involved 30 English teachers from 22 junior high schools. The study found out that most teachers perceived their online classes as quite effective. However one third of them reported online classes as less effective. All teachers also reported problems in their online classes. This suggests online teaching practiced by English teachers in Pekalongan varied in effectiveness. Each teacher also encountered problems in managing online classes and this suggests an urgent need to help teachers to minimize those problems. Keywords: online teaching, English, pandemic time